Effect of interval training in the competitive period on anaerobic capacity in judo athletes - Norkowski, H.; Borowiak, W.; Sikorski, W.; Sledziewski, D. (Journal of Combat Sports and Martial Arts, 2014)
Background. The aim of the study was to evaluate the effect of interval training on cycle ergometer on relative values of mechanical work (J/kg), peak power (W/kg) and time of work (s) at the level of 97.5% of peak power during 6 repetitions of exercise on cycle ergometer. Material and methods. Ten judo athletes randomly divided into two groups performed 5-week training programs. Before each judo training session, the experimental group (n=5) performed an additional training session on cycle ergometer in the form of six 10-second maximum efforts divided with periods of passive rest (45s each). The control group (n=5) performed a standard judo training typical of the competitive period. Results. Comparison of the results obtained for the experimental and control groups at the end of the competitive period demonstrated that mean mechanical work (J/kg), peak power (W/kg) and time of work (s) at the level of 97.5% of peak power in each of six test efforts in the group that performed additional exercise on cycle ergometer were significantly higher than in the control group that participated in a standard judo training program. Conclusions. Regular interval training sessions on cycle ergometer during the competitive period in judo is effective in maintaining high level of anaerobic capacity over a longer period of time.